The Appropriate Acyclic Precursors to Build Biologically Active 5-acylamino-1,3-thiazoles - Mara Tomassetti; Gabriele Lupidi; Serena Gabrielli; Federico Vittorio Rossi; Samuele Lillini; Gianluca Bianchini; Andrea Aramini; Daniele Canestrari; Enrico Marcantoni (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
The aim of this opinion article is to highlight the trends in the development of efficient catalyst-free synthesis of the Hantzsch polysubstituted 1,3-thiazoles. They are heterocycles of particular importance in the pharmaceutical industry, and the strategy involves the cyclization reaction of acyclic precursors with minimum auxiliary substances, toxic reagents, organic solvents, and disposal problems.